2018
DOI: 10.1097/md.0000000000011992
|View full text |Cite
|
Sign up to set email alerts
|

Association between sleep disorders and subsequent chronic spontaneous urticaria development

Abstract: Patients with chronic spontaneous urticaria (CSU) often have sleep disorders (SDs) because of pruritus. However, SDs might also contribute to the development of CSU. Here, we present the first population-based cohort study on the association between SDs and subsequent CSU development.This study investigated whether SDs increase the risk of CSU by using a population-based database in Taiwan.This retrospective matched-cohort study included 105,892 patients with new-onset SDs (SD cohort) and 105,892 randomly sele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0
4

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(30 citation statements)
references
References 35 publications
0
22
0
4
Order By: Relevance
“…Chronic spontaneous urticaria is a chronic disease, which worsens the quality of life, disturbs daily activities and sleep pattern because of pruritus and causes emotional disorders and social isolation [11,12]. Several studies indicate that CU has a significant impact on patient's psychological state.…”
Section: Discussionmentioning
confidence: 99%
“…Chronic spontaneous urticaria is a chronic disease, which worsens the quality of life, disturbs daily activities and sleep pattern because of pruritus and causes emotional disorders and social isolation [11,12]. Several studies indicate that CU has a significant impact on patient's psychological state.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the wide-ranging spectrum that sleep-related breathing disorders represent, few studies have explored the association between obstructive sleep apnea (OSA) and CU. 12 , 13 For instance, a previous study found that 40% of CU patients had OSA assessed through polysomnography, a rate which appears higher than reported for the general population. 14 It is still unclear whether CU increases the risk for developing OSA, or the latter increases the risk for CU.…”
Section: Introductionmentioning
confidence: 98%
“… 14 It is still unclear whether CU increases the risk for developing OSA, or the latter increases the risk for CU. 13 There are many unanswered questions including what the risk is for OSA among CU patients and its influence on CU disease severity and control. Thus, this study aims to expand the current knowledge on OSA and CU by determining in a sample cohort of Latin American CU patients, the frequency of risk categories for undiagnosed OSA and how they might correlate with CU clinical and patient reported outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…In a previous cohort study, 46% of patients with urticaria had sleep apnea and this rate was similar to our study. 8 To the best of our knowledge, there are no studies showing the relationship between urticaria severity and AHI.…”
Section: T a B L E 1 The Characteristics And Psg Findings Of Study Pamentioning
confidence: 99%
“…6 There have been a few studies examining the relationship between urticaria and OSAS. 7,8 In addition, to the best of our knowledge, one of the study was cohort study, and the other one did not have control group and there have been no case-controlled study that detected sleep apne disorders in chronic urticaria patients. In this study, we aimed to investigate the relationship between urticaria and OSAS.…”
Section: Introductionmentioning
confidence: 99%